Corneometric features in atopic dermatitis under the conditions of filaggrin dysmorphism in children - O. V. Reshetylo (Journal of Education, Health and Sport, 2018)
The objective: to study the morpho-functional state of the skin in atopic dermatitis in children, taking into account the polymorphism of filaggrin protein genes. Materials and methods. 111 children with atopic dermatitis (AD) aged 3 - 11 years old were examined. In addition to general-clinical and allergic examination, a molecular-genetic analysis was conducted to detect polymorphism in the filaggrin gene (FLG). The hydration of the skin was measured by corneometry. Statistical processing of the material was performed using Statistica software 6. Results. It has been established that in 51 AD children (45.9% ± 6.98) polymorphism of FLG took place. Mutation of R501X occurred in 40 children (78.4 ± 5.76%), polymorphism of 2282del4 had 4 patients (7.8 ± 3.76%), combined variant of R501X and 2282del4 took place in 7 (13.7 ± 4.81%) patients. The influence of FLG structural changes on the morpho-functional state of the skin was revealed. It was reflected by a significant decrease in the moisture content of the epidermis (p